Identifikasi Atraksi Wisata Edutourism di Kampung Adat Kuta - Andien Moya Saharani; Riswandha Risang Aji (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Tourism is currently developing not only as a means of recreation, but also as a medium for learning through the concept of edutourism. Kuta Traditional Village in Ciamis Regency is an area that still upholds traditions, spiritual values, and environmental sustainability, making it a potential destination for educational tourism. However, this potential has not been fully realized due to the lack of a comprehensive identification of educational tourism attractions. This study aims to identify and describe tourism attractions that can support the development of edutourism. The research method used is a qualitative approach with a case study, through field observations and semi-structured interviews with traditional leaders and local communities. The research findings identified various educational attractions such as the sacred forest trail, the Nyuguh traditional ceremony, traditional palm sugar processing, Kamuti bag making, Klanceng honey bee farming, compost production, and traditional Gondang Buhun and Ronggeng Tayub performances. These attractions contain educational values related to environmental conservation, culture, spirituality, and local economy. These findings indicate that the Kuta Traditional Village has significant potential as an edutourism destination rooted in local wisdom and can serve as a foundation for the development of sustainable and participatory educational tourism. Abstrak. Pariwisata saat ini berkembang tidak hanya sebagai sarana rekreasi, tetapi juga sebagai media pembelajaran melalui konsep edutourism. Kampung Adat Kuta di Kabupaten Ciamis merupakan kawasan yang masih memegang teguh tradisi, nilai spiritual, dan kelestarian lingkungan sehingga berpotensi menjadi destinasi wisata edukatif. Namun, potensi ini belum tergarap optimal karena belum adanya identifikasi menyeluruh terhadap atraksi wisata bernilai edukasi. Penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan atraksi wisata yang dapat mendukung pengembangan edutourism. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan studi kasus, melalui observasi lapangan dan wawancara semi-terstruktur dengan tokoh adat dan masyarakat setempat. Hasil penelitian menemukan berbagai atraksi edukatif seperti napak tilas hutan keramat, prosesi adat Nyuguh, pengolahan gula aren tradisional, pembuatan tas kamuti, budidaya lebah madu klanceng, produksi pupuk kompos, serta pertunjukan seni tradisional Gondang Buhun dan Ronggeng Tayub. Atraksi-atraksi tersebut memuat nilai pembelajaran tentang pelestarian alam, budaya, spiritualitas, dan ekonomi lokal. Temuan ini menunjukkan bahwa Kampung Adat Kuta memiliki potensi besar sebagai destinasi edutourism berbasis kearifan lokal dan dapat menjadi dasar bagi pengembangan wisata edukatif yang berkelanjutan serta partisipatif.